Impact of Various Soil and Water Conservation Measure, in different Micro-watersheds on retention of Sediment and Soil Nutrients - A Case Study in Panchkula District, Haryana - R.P.Yadav,; R.k. Aggarwal,; V.S. Katiyar,; Y. Agnihotri, (Journal of Soil and Water Conservation, 2022)
Three micro-watersheds treated under NWDPRA during VIII Five Year Plan in Panchkula district of Haryana were studied for effectiveness of various soil conservation measures. Treatment of drainage line to control erosion received major emphasis. Accordingly 620 brushwood check dams (BWD), 959 loose boulder check dams (LBCD), 107 earthen gully plugs (EGP) and 138 small and medium size dugout sunken ponds (DSP) were constructed in various reaches of the watersheds in the years 1992-94. Survival percentage, effectiveness, sediment amount and quality retained behind these structures were worked out during evaluation after five year of implementation. Survival percentage ranged from 0 to 86 in different mechanical and vegetative structures: lowest being with brushwood check dams and highest with dugout sunken ponds. Amount of sediment retained per structure for 5 years was found to be 3, 68 and 99 m* for loose boulder check dams, dugout sunken ponds and earthen gully plugs, respectively. However, for organic matter and nutrient retention the order was: DSP>EGP>LBCD.